Cigarette or E-Cigarette Use as Strong Risk Factors for Heated Tobacco Product Use among Korean Adolescents - Hwang, Jun Hyun (Int J Environ Res Public Health, 2020)
Heated tobacco products (HTPs) were first introduced in Korea in June 2017. This study examined the prevalence of current HTP use among Korean adolescents and its association with conventional cigarette (CC) or electronic cigarette (EC) use. The study analyzed nationally representative data (the 2019 Korea Youth Risk Behavior Web-based Survey) from a sample of 57,303 Korean students from grades 7–12. Multinomial logistic regression models were designed to evaluate the association between EC or CC use and HTP use. A total of 2.6% of respondents were current HTP users and 95.9% of them were dual or triple users of CC or EC. The likelihood of HTP use was higher among current CC or EC users and highest among dual users. When the association between each tobacco product and current HTP use was analyzed, the dual use tendency of HTPs and other products steadily increased with the increase of CC or EC smoking frequency. Adolescents who use ECs and/or CCs are likely to use HTPs. Thus, HTPs could be a new public health concern for adolescents in terms of dual or triple use patterns of CC or EC.